2019
DOI: 10.1002/em.22333
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid Genotoxicity: Correlation of the Pig‐a Assay with Regulatory Genetic Toxicology In Vivo Endpoints

Abstract: Caffeic acid is found in variety of fruits and vegetables. It is considered as possible human carcinogen (Group 2B). It is negative in Ames and mouse micronucleus (MN), but positive in mouse lymphoma and chromosomal aberration assays. The objective of this study was to evaluate the in vivo genotoxicity of caffeic acid using three different endpoints: in vivo MN, Pig‐a, and comet assay. Two sets of six rats per group were administered vehicle (0.5% hydroxypropyl methylcellulose), 500, 1,000, or 2,000 mg/kg/day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…For example, Bhalli, et al evaluated the genotoxic potential of caffeic acid in vivo through the micronucleus assay and the comet assay. Results showed that, through the MN assay, caffeic acid generated a genotoxic effect by increasing the number of micronucleated cells; however, the comet assay did not demonstrate a significant increase in the number of cells with DNA damage [ 47 ]. C. oxyacantha leaves contain vitexin, isovitexin, and orientin.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bhalli, et al evaluated the genotoxic potential of caffeic acid in vivo through the micronucleus assay and the comet assay. Results showed that, through the MN assay, caffeic acid generated a genotoxic effect by increasing the number of micronucleated cells; however, the comet assay did not demonstrate a significant increase in the number of cells with DNA damage [ 47 ]. C. oxyacantha leaves contain vitexin, isovitexin, and orientin.…”
Section: Discussionmentioning
confidence: 99%
“…However, this phenomenon was not reported in recent studies. Dose of up to 2,000 mg/kg/day CA on rats did not result in gene mutations in Pig‐a assay and blood or liver DNA damage (Bhalli et al., 2019). Similarly, Amano et al.…”
Section: Potential Safety Concerns From Hca Intakementioning
confidence: 99%
“…On the other hand, caffeic acid (2.46%) which is one of the major compounds of TEE from A. hypogaea, showed absence of genotoxicity in other researches. Bhalli et al (2019) demonstrated that 1000 mg/kg b.w. of caffeic acid was not genotoxic using micronuclei test and comet assay.…”
Section: Identification Of the Tegument And Seed Of Peanut Compoundsmentioning
confidence: 99%